Agentive Apprenticeship of Observation and English Teacher Identity: A Pakistani Case of Learning to Teach English - Channa, Liaquat Ali (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée)

(untitled) (University of New Brunswick, 2020)
An exploration of literature on second/foreign language (L2/FL) teaching suggests that the phenomenon in question has been investigated either by examining classroom processes or by exploring teachers’ lived experiences. Situated in the latter area, this paper reports a qualitative study that understands how Pakistani primary school teachers learn to teach English—the subject mandated in recent curricular reforms—and develop their English teacher identity. The findings problematize the apprenticeship of observation concept and demonstrate that the teachers agentively draw upon their favorite English learning experiences. They teach English not the way they were taught, rather, they teach the way they loved learning English. Thus, they develop the English teacher identities they adored while they were students. The paper presents pertinent implications.